Understanding child disadvantage from a social determinants perspective. Issue 3 (20th December 2017) - Goldfeld, Sharon; O'Connor, Meredith; Cloney, Dan; Gray, Sarah; Redmond, Gerry; Badland, Hannah; Williams, Katrina; Mensah, Fiona; Woolfenden, Sue; Kvalsvig, Amanda; Kochanoff, Anita T
Abstract : Background: Child health and developmental inequities exist in all countries. Comprehensive and robust concepts of disadvantage are fundamental to growing an evidence base that can reveal the extent of inequities in childhood, and identify modifiable leverage points for change. We conceptualise and test a multidimensional framework of child disadvantage aligned to a social determinants and bioecological perspective. Methods: The Longitudinal Study of Australian Children is a nationally representative sample of two cohorts of Australian children, including the birth cohort of 5107 infants, which commenced in May 2004. The analysis focused on disadvantage indicators collected at age 4–5 years. Confirmatory factor analysis was used to test a theoretically informed model of disadvantage. Concurrent validity was examined through associations with academic performance at 8–9 years. Results: The model comprising four latent factors of sociodemographic (10 indicators), geographical environments (three indicators), health conditions (three indicators) and risk factors (14 indicators) was found to provide a better fit for the data than alternative models. Each factor was associated with academic performance, providing evidence of concurrent validity. Conclusion: The study provides a theoretically informed and empirically tested framework for operationalising relative child disadvantage. Understanding and addressing inequities will be facilitated by capturing the complexity of children's experiences of disadvantage across the multiple environments in which their development unfolds.